Research Activities of the IMF, January 1991-December 1998. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
A selective index of major research papers prepared by IMF staff in 1991-98.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Labor Economics